MAINTENANCE CENTERED ON EXERGY AND EXERGOECONOMIC INDICATORS OF A PREHEAT TRAIN OF A CRUDE OIL DISTILLATION UNIT (2022)
Established or create new ones to plan the cleaning tasks of the heat exchangers. In this work, a maintenance strategy is developed for a preheating train under the Maintenance Centered on Energy Efficiency (MCEE) philosophy, where it is sought to integrate the information of the principles of the second law of thermodynamics with economic variables to use parameters. The modification of the maintenance justification parameter (J) is proposed, adding to the introduction of two new maintenance indicators (W and X). Each one seeks to evaluate an essential criterion for the maintenance area: economic viability, technical feasibility, and benefits. Towards the other exchangers in the network after cleaning a specific component. A criticality diagram and a criticality matrix are used. The heat exchangers are grouped into sub-assemblies, with the leading group consisting of the key heat exchangers (KHEX), the elements of which have a significant impact on the efficiency of the preheat train. For their part, the regions are composed of components whose performance is less considerable than that of the KHEX. In total, 34 maintenance activities will be carried out, distributed among the 25 interchanges of the network. The planning of a program of cleaning activities according to the maintenance strategy based on the philosophy of the MCEE establishes a substantial scientific contribution due to the almost null existence of exergetic studies applied to the management of maintenance tasks and focused mainly on the preheating of trains. Copyright © 2022 by ASME.